Factors associated with self-reported discrimination against men who have sex with men in Brazil. - Magno, Laio (2017)
OBJECTIVE: To estimate self-reported discrimination due to sexual orientation among men who have sex with men (MSM) in Brazil and to analyze associated factors. METHODS: A cross-sectional study of 3,859 MSM recruited in 2008–2009 with respondent driven sampling. Data collection conducted in health centers in 10 Brazilian cities. A face-to-face questionnaire was used and rapid HIV and syphilis tests conducted. Aggregated data were weighted and adjusted odds ratio estimated to measure the association between selected factors and self-reported discrimination due to sexual orientation. RESULTS: The sample was predominantly young, eight plus years of schooling, pardo (brown), single, low-income, and identified themselves as gay or homosexual. The prevalence of self-reported discrimination due to sexual orientation was 27.7% (95%CI 26.2–29.1). Discrimination was independently associated with: age < 30 years, more years of schooling, community involvement and support, history of sexual and physical violence, suicidal thoughts, and unprotected receptive anal intercourse. CONCLUSIONS: The prevalence of self-reported discrimination among MSM in Brazil is high. These results challenge the assumptions that MSM-specific prevention and support programs are not required or that health professionals do not need special training to address MSM needs.